Promising Drugs Targeting Specific Mechanisms of Deregulation in T Cell Lineage Acute Lymphoblastic Leukemia - Xavier Thomas (Oncology and Therapy)
Abstract T cell acute lymphoblastic leukemia (T-ALL) is a class of hematological malignancies predominantly affecting children, adolescents, and young adults, marked by aggressive behavior and poor clinical response, especially in relapsing cases. Advances in molecular biology for the last decade have led to the identification of potential targetable alterations, which should lead to the development of new therapies. T oncogenesis involves not only overexpression of some oncogenes, but also deregulation of some signaling pathways, epigenetic mechanisms, and apoptosis. The present review presents the promising therapeutic agents targeting these specific alterations involved in the development of T-ALL.